Early-life antibiotics attenuate regulatory T cell generation and increase the severity of murine house dust mite-induced asthma. (September 2018) - Adami, Alexander; Bracken, Sonali; Guernsey, Linda; Rafti, Ektor; Maas, Kendra; Graf, Joerg; Matson, Adam; Thrall, Roger; Schramm, Craig
Abstract Introduction Early-life exposure to antibiotics (ABX) has been linked to increases in asthma severity and prevalence in both children and laboratory animals. We explored the immunologic mechanisms behind this association using a mouse model of house dust mite (HDM)-induced asthma and early-life ABX exposure. Methods Mice were exposed to three short courses of ABX following weaning and experimental asthma was thereafter induced. Airway cell counts and differentials; serum immunoglobulin E (IgE); pulmonary function; lung histopathology; pulmonary regulatory T cells (Tregs); and the fecal microbiome were characterized following ABX exposure and induction of experimental asthma. Results Asthma severity was increased in mice exposed to ABX, including: airway eosinophilia, airway hyper-reactivity, serum HDM-specific IgE, and lung histopathology. ABX treatment led to sharp reduction in fecal microbiome diversity, including the loss of pro-regulatory organisms such as Lachnospira. Pulmonary Tregs were reduced with ABX treatment, and this reduction was directly proportional to diminished microbiome diversity. Conclusion Intermittent exposure to ABX early in life worsened the severity of experimental asthma and reduced pulmonary Tregs; the latter change correlated with decreased microbiome diversity. These data may suggest targets for immunologic or probiotic therapy to counteract the harmful effects of childhood ABX.